The effect of cooling time of the injection moldings on the thermodynamic equation of state - Kowalska, B.; Sikora, R. (Polimery, 2022)
The dependencies between the pressure (p, in the range 0.1-120 MPa), specific volume (v) and temperature (T) during the isobaric cooling of polypropylene injection moldings, obtained after various cooling time in the mold cavity (11s, 20s or 29s) [15] have been investigated. The results of investigations were presented in the p-v-T graphs (Figs. 2-4). On this basis the constants in the thermodynamic equation of state by Tait as well as in the IKV equation have been determined; these constants have been determined for solid and molten state of PP in relation to cooling time of moldings (Tables 3-6). The assessment of the values of relative errors of approximation has been done using two discussed equations, from the point of view of their application to the description of the courses of curves in p-v-T graphs, obtained on the basis of measurements (Tables 2 and 5). The effect of cooling time of injection moldings on the course of curves describing the dependencies of specific volume on the temperature has been also analyzed.